Reliability analysis of dynamic fault trees with Priority-AND gates based on irrelevance coverage model. (August 2022) - Zhou, Siwei; Ye, Luyao; Xiong, Shengwu; Xiang, Jianwen
Abstract: The irrelevance coverage model (ICM) is an extension of the imperfect fault coverage model (IFCM), which can reduce the risk of uncovered component failures by isolating irrelevant components in systems. However, the ICM has been limited to static systems so far. To address this issue, we extend the ICM to dynamic systems modeled by dynamic fault trees (DFTs) with Priority-AND (PAND) gates. The component irrelevance is analyzed in the DFTs, which shows a component could become irrelevant due to specific sequence failures of some other components, and the implication of irrelevancy may differ from that in static systems. The definition of minimal irrelevance triggers (MITs) and the reduction rules are introduced based on the temporal algebraic framework. The sum of disjoint products (SDP) method is further applied for the quantitative analysis of system reliability. Case studies demonstrate the effectiveness of our method. Furthermore, the ICM can also play a role in the dynamic systems in terms of reliability improvement compared to the IFCM. Highlights: The possible change of component relevancy in the PAND gate is firstly addressed in this paper. The concept of minimal irrelevance trigger is redefined for dynamic fault trees. The irrelevance coverage model is extended from static fault trees to dynamic fault trees accordingly by using algebraic structure-functions.